PROCRASTINATION BEHAVIOR AND LIFE ROUTINES AMONG STUDENTS IN KERALA - K. MANIKANDAN AND SEBIN. P (ACADEMICIA: An International Multidisciplinary Research Journal, 2013)
The purpose of the study is to investigate the procrastination behavior of students in relation to certain life routines such as studying daily, doing assignments properly, punctuality in studies, waking up the morning for studies, completing studies before sleeping, etc., and also with some demographic variables. The participants were 560 students studying at different educational institutions (SSLC to Post graduation) from Kerala state, India including both boys and girls. Their age ranges from 14 to 24. The analysis revealed that there exist significant interaction between sex and class of study on procrastination and exist significant difference between males and females on the variable procrastination. It also revealed that the life routine of the students has a significant association with procrastination behavior.